Detection of Counterfeit Tequila by Fluorescence Spectroscopy - de la Rosa Vázquez, José Manuel; Fabila-Bustos, Diego Adrián; Quintanar-Hernández, Luis Felipe de Jesús; Valor, Alma; Stolik, Suren (Journal of Spectroscopy, 2015)
An ultraviolet (UV) light induced fluorescence study to discriminate fake tequila from genuine ones is presented. A portable homemade system based on four light emitting diodes (LEDs) from 255 to 405 nm and a miniature spectrometer was used. It has been shown that unlike fake and silver tequila, which produce weak fluorescence signal, genuine mixed, rested, and aged tequilas show high fluorescence emission in the range from 400 to 750 nm. The fluorescence intensity grows with aging in 100% agave tequila. Such fluorescence differences can even be observed with naked eyes. The presented results demonstrate that the fluorescence measurement could be a good method to detect counterfeit tequila.